The World Bank's structural adjustment loans: a critique - Rasul Shams (Intereconomics, 1988)
Following the introduction of its structural adjustment loans the World Bank became the object of the criticism that had until then been directed only at the IMF and its stabilisation and adjustment programmes. This article shows that structural adjustment loans do in fact take the traditional criticism into account. It then proceeds to analyse the various interests involved in order to highlight the constraints to which the Bank is subject in the formulation of its policy.
Keywords: 330; World Bank